Desenvolvimento de vidros ao chumbo utilizando resíduos de rochas ornamentais - Campos, Daina Bourguignon (2023)
The ornamental stone sector is responsible for generating a large amount of waste throughout the world. These wastes are rich in oxides that can be used as raw materials in the manufacture of glass. In general, they have a high concentration of SiO2, an oxide that forms a glass network. From this perspective, this work aimed to develop lead glass, also known commercially as lead crystals, from the use of silicate wastes from ornamental stones processed on diamond multiwire looms, as well as characterizing the waste and glass produced. The methodology used was fusion/cooling. The maximum process temperature was 1500°C with a time of 3 hours. The results of this work were the development of two glasses using granite and quartzite wastes, adding lead in the form of lead monoxide and other carbonates in sufficient quantities to adjust the typical compositions of the necessary oxides. All results were compared with a commercial glass sample. X-ray diffractions (XRD) showed complete vitrification of the glasses produced; FRX showed characteristics similar to the lead crystal glass pattern; the densities presented approximate values and the hydrolytic resistance was classified as average in the two glasses produced, according to the ISO 719 standard. The iron content present in the glass produced with granite resulted in a glass with a greenish color, while the quartzite glass presented a bluish color, most likely, due to the titanium oxide present in its composition. It was concluded that there is technical feasibility in the production of glass using ornamental stones waste to replace silica from sand.